Short-term efficacy of music therapy combined with α binaural beat therapy in disorders of consciousness - Liu, Zi-Bo; Liu, Yan-Song; Zhao, Long; Li, Man-Yu; Liu, Chun-Hui; Zhang, Chun-Xia; Li, Hong-Ling (Frontiers in Psychology, 2022)
Objective To investigate the short-term effect of music therapy combined with binaural frequency difference therapy on patients with consciousness disorder. Materials and methods Ninety patients with definite diagnosis of disorders of consciousness (DOC) were selected. These patients were randomly divided into control group, experiment 1 group and experiment 2 group, with 30 patients in each group. The control group was treated with routine clinical treatment and rehabilitation. In experiment 1 group, music therapy was added to the control group. In experimental group 2, music therapy combined with binaural α frequency difference therapy was added to the control group. All patients were assessed before and after 30 treatments. The assessment items included Glasgow Coma Scale (GCS), Coma Recovery Scale revised (CRS-R), electroencephalogram (EEG), upper somatosensory evoked potential (USEP), and brainstem auditory evoked potential (BAEP). Results Before treatment, there were no significant differences in GCS score, CRS-R score, USEP, BAEP, and EEG scores among the three groups (P > 0.05). After 30 times of treatment, GCS score, CRS-R score, USEP, BAEP, and EEG scores in 3 groups were significantly higher than those before treatment (P < 0.05), and experimental group 2 >experimental group 1 >control group (P < 0.05). And the consciousness rate of experimental group 2 was better than experimental group 1, experimental group 1 was better than the control group and the difference was statistically significant (P < 0.05). Conclusion Music therapy combined with binaural α frequency difference therapy is more effective in stimulating DOC patients.